Strategies for thorium fuel cycle transition in the SD-TMSR. (1st December 2020) - Ashraf, O.; Rykhlevskii, Andrei; Tikhomirov, G.V.; Huff, Kathryn D.
Highlights: Five initial fissile loadings were studied for transitioning to the thorium fuel cycle The MSR burnup routine was used to simulate the online reprocessing and refueling. The dynamics of k eff and essential safety parameters were investigated in this work. The neutron energy spectrum shift during the reactor operation was calculated. Temperature coefficient of reactivity evolution during SD-TMSR operation was investigated. Abstract: Liquid-fueled Molten Salt Reactor (MSR) systems represent advances in safety, economics, and sustainability. The MSR has been designed to operate with a Th/ 233 U fuel cycle with 233 U used as startup fissile material. Since 233 U does not exist in nature, we must examine other available fissile materials to start up these reactor concepts. This work investigates the fuel cycle and neutronics performance of the Single-fluid Double-zone Thorium-based Molten Salt Reactor (SD-TMSR) with different fissile material loadings at startup: High Assay Low Enriched Uranium (HALEU) (19.79%), Pu mixed with HALEU (19.79%), reactor-grade Pu (a mixture of Pu isotopes chemically extracted from Pressurized Water Reactor (PWR) spent nuclear fuel (SNF) with 33 GWd / tHM burnup), transuranic elements (TRU) from Light Water Reactor (LWR) SNF, and 233 U. The MSR burnup routine provided by SERPENT-2 is used to simulate the online reprocessing and refueling in the SD-TMSR. The effective multiplication factor, fuel salt composition evolution, and net production of 233 U are studied in the present work. Additionally, the neutron spectrum shift during the reactor operation is calculated. The results show that the continuous flow of reactor-grade Pu helps transition to the thorium fuel cycle within a relatively short time (≈ 4.5 years) compared to 26 years for 233 U startup fuel. Finally, using TRU as the initial fuel materials offers the possibility of operating the SD-TMSR for an extended period of time (≈40 years) without any external feed of 233 U.